Karakteristik Batako Menggunakan Pozolan Organik Dalam Menciptakan Green Material - Nur Anny S. Taufieq; Irma Aswani Ahmad; Akshari Tahir Lopa (Seminar Nasional LP2M UNM, 2021)
Abstract.  One of the wastes that can be utilized is Rice Husk Ash (ASP). Rice husk ash is a waste material from processing rice into rice in rice mills, which is not used for further processing. As a waste material for processing mills, rice husk ash is an alternative additive that can substitute for cement. This study aims to determine the characteristics of Rice Husk Ash (ASP) as a cement substitution material in making bricks and to determine the characteristics of rice husk ash (ASP) as a cement substitution material. The results showed that the specimens with ASP 3% contained high SiO2 compounds, namely 60.81%. The test object with 5% ASP contains 40.32% CaO compound. And the test object with ASP 7% contains CaO compound of 32.58%.Keywords: Brick, rice husk ash (ASP)